Intersectional approaches to the experiences of parents of a child with a disability in Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Arts, Massey University, New Zealand - Kim, Yeseul (Massey University, 2022)
This study aims to investigate the intersectional experiences of parents caring for a child with a disability in Aotearoa New Zealand, highlighting the challenges faced by these parents. Drawing on critical race theory, social constructionism, and interpretative phenomenological analysis, the research delves into the unique context of New Zealand, uncovering issues such as pathologized difficulties like depression and anxiety, the poverty trap, communication barriers, experiences of solo mothers, racism, housing insecurity, and relinquishment. The findings highlighted an intricate cyclical process reflecting the experiences faced by parents of children with disabilities and communication difficulties. The analysis builds on previously discussed findings to elucidate the "Repeat" cycle, a construct encompassing seven interconnected elements: pathologising difficulties, the poverty trap, loss and isolation, racial discrimination, housing insecurity, the inclination to capitulate, and the perpetuation of the cycle. The interconnectivity of the findings reveals that the parents' experiences embody a cyclical process. The "Repeat" cycle underscores the manner in which one aspect of their experience can give rise to another, culminating in a self-sustaining cycle that perpetuates and intensifies the challenges faced by these parents. The study proposes practical recommendations to address the issues of families with children with disabilities, including depathologising the difficulties, eradicating poverty, fostering inclusive practices, abolishing punitive approaches to disability for solo parents, promoting anti-racism, and ensuring accessible and affordable housing solutions. This study contributes to the existing literature on the intersectional experiences of parents of children with disabilities and offers valuable insights into the unique context of Aotearoa New Zealand, paving the way for a more inclusive and supportive society for families with children with disabilities. The research acknowledges its limitations and encourages further exploration of additional perspectives to better support these families in the future.
Keywords: 520302 Clinical psychology; 420318 People with disability